A Direct Search Method to Locate Negative Cycles in a Graph - Florian, M.; Robert, P. (Management Science, 1971)
A direct search method for locating and tracing negative cycles in a graph is developed based on a property of real, finite sequences. The efficiency of the method and its application for computing minimum cost flows is tested by applying it to solve a series of assignment problems.